Importance of Management of Radioactive ResiduesiIn Iodotherapy (Revista Brasileira Multidisciplinar, 2008)
Iodotherapy is one of the medicinal nuclear therapeutics that employs radioactive iodine as the radionuclide. This treatment, carried out in hospitals, requires radioprotection procedures to guard the patients, the medical team and the environment against contamination. A discussion regarding the application of this therapeutic shows the importance of implanting programs to manage radioactive residues which are generated in hospital units.
Keywords: Iodotherapy; Nuclear Medicine; Radioactive Residues.